Pengaruh Brand Ambassador, Product Quality, Dan Kebanggaan Merek Lokal Terhadap Keputusan Pembelian (Purchase Decision) Emina Cosmetics Di Surakarta Dengan Purchase Intention Sebagai Variabel Mediasi - Sabrina Rohqayati; Wuryaningsih Dwi Lestari (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyze the influence of brand ambassador, product quality, and local brand pride on the purchase decision of Emina Cosmetics in Surakarta, with purchase intention as a mediating variable. The research employs a quantitative method using Partial Least Square-Structural Equation Modeling (PLS-SEM). Data were collected through a Likert-scale questionnaire survey from 150 respondents selected using purposive sampling. The results indicate that brand ambassador and local brand pride do not significantly affect purchase intention or purchase decision. Conversely, product quality has a significant positive influence on both variables. Additionally, purchase intention does not mediate the relationship between independent variables and purchase decision. These findings provide insights for companies to optimize marketing strategies. Future research is suggested to add other influential variables and expand the respondent coverage.